Prolonged Intake of Levonorgestrel Oral Contraceptive Caused an Increase in Tumor Necrosis Factor Alpha, Nuclear Factor -Kappa B and Oxidative Stress Biomarkers in the Uterus and Ovary of Female Wistar Rats - ADENIJI, Catherine B.; IGHODARO, Osasenaga M.; OKHUAKHUA, Shalom O.; OYERINDE, Abiodun O. (Journal of Science, Technology and Innovation Research, 2025)
The incessant use of contraceptives among young adults is a cause for concern. This study assessed the levels of some proinflammatory and oxidative stress biomarkers associated with incessant intake of levonorgestrel (LNG) in the uterus and ovaries and the outcome of drug withdrawal using a rat model. Sixty female Wistar rats weighing 110-120 g were randomized into three groups (n = 20). Groups A and B were administered 1.83 mg/kg body weight (BW) of LNG orally once and twice weekly, respectively, while group C served as the control. Five animals from each group were sacrificed at 30, 60, and 90 days. The remaining were observed for 30 days post-treatment to assess possible recovery. The serum levels of tumor necrosis factor alpha (TNF-α) and nuclear factor kappa B (NF-kβ) were determined using the ELISA technique. Oxidative stress biomarkers such as catalase (CAT), reduced glutathione (GSH), glutathione peroxidase (GPx), glutathione-S-transferase (GST), superoxide dismutase (SOD), reduced glutathione (GSH) and lipid peroxidation (LPO) in the uterus and ovaries were determined using standard procedures. Results showed an increase in TNF-α and NF-kB, especially in the group administered LNG twice-weekly. There was a significant reduction in CAT, GSH, SOD, and GPx in both organs. The GST and MDA were significantly elevated, especially in the uterus. Recovery was observed only in TNF-α, GSH, and GPx in the ovary of the once-weekly group. The uterus was more affected, and animals exposed to LNG twice-weekly suffered more assaults. The ability of the animals to recover following drug withdrawal was observed in the once-weekly treated group and in the ovary.